1995
DOI: 10.1006/excr.1995.1239
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heat Shock Protein 90 (hsp90) in Neural and Nonneural Tissues of the Control and Hyperthermic Rabbit

Abstract: Tissue-specific differences were apparent in the constitutive level of hsp90 in various body tissues of the unstressed rabbit. Western blotting with monoclonal antibody 29A revealed very low levels in muscle and highest levels in neural regions (cerebellum, cerebral hemispheres, and retina) and in testes and thymus. Intermediate levels were apparent in other tissues such as liver, kidney, heart, and small intestine. Following hyperthermia, induction of hsp90 was not detected with 1-D Western blotting in tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
13
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 0 publications
5
13
0
Order By: Relevance
“…To our knowledge no in vivo studies have described changes in the levels and distribution of the heat shock protein HSP-90 in several rat brain regions analyzed after acute controlled exposure of the animals to 2.45 GHz at non thermal SAR in a GTEM cell (see Tables 2, 3). In this study, we found that at 90 minutes post-irradiation, there was an increase in cellular HSP-90 and the same regional pattern of distribution was observed as in the cerebral cortex of non-irradiated rats [12] as also observed with other stimuli such as hyperthermia [39,40] anoxia [41] and alcohol [42]. As the cortex is the uppermost part of the brain structure, it may initially be the most strongly affected [43] in relation to the energy of non-ionizing radiation that the tissue absorbs -expressed as the specific absorption rate (SAR).…”
Section: Discussionsupporting
confidence: 76%
“…To our knowledge no in vivo studies have described changes in the levels and distribution of the heat shock protein HSP-90 in several rat brain regions analyzed after acute controlled exposure of the animals to 2.45 GHz at non thermal SAR in a GTEM cell (see Tables 2, 3). In this study, we found that at 90 minutes post-irradiation, there was an increase in cellular HSP-90 and the same regional pattern of distribution was observed as in the cerebral cortex of non-irradiated rats [12] as also observed with other stimuli such as hyperthermia [39,40] anoxia [41] and alcohol [42]. As the cortex is the uppermost part of the brain structure, it may initially be the most strongly affected [43] in relation to the energy of non-ionizing radiation that the tissue absorbs -expressed as the specific absorption rate (SAR).…”
Section: Discussionsupporting
confidence: 76%
“…Hsp90 is a protein that is widely distributed in the retina in various animals (Quraishi and Brown, 1995;Song and Sokolov, 2009) and is involved in maintaining stability of the junction between Müller cells and photoreceptor cells in the retina (Dean and Tytell, 2001). Furthermore, Hsp90 regulates proliferation and death of retinal cells (Arruda-Carvalho et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there was an upregulation in expression of five specific proteins in turtle hepatocytes under anoxia or heat shock but these proteins were not rigorously identified (Land and Hochachka, 1995). Heat shock proteins (Hsps) have been considered as possible candidates, since their expression is induced by various stresses such as hyperthermia, radiation, heavy metals, ischemia, anoxia and reoxygenation in anoxia-sensitive models (Airaksinen et al, 1998;Manzerra et al, 1997;Quraishi and Brown, 1995). Chang et al (2000) provided the first evidence of increased Hsp70 expression in painted turtle myocardium subjected to a 12·h forced dive, but the antibody they used did not distinguish between the constitutive (Hsp73) and inducible (Hsp72) isoform.…”
mentioning
confidence: 99%
“…Similarly to Hsp70, Hsp90 expression is induced in the stressed cell (Kawagoe et al, 2001;Quraishi and Brown, 1995), where it binds to partially unfolded proteins, holding them in a folding-competent state until other chaperones, such as Hsp70, are recruited to help restore the original structure of the protein.…”
mentioning
confidence: 99%